EPR OF A HYDROGEN/DOUBLE-LITHIUM CENTRE IN α-QUARTZ - Lees N.S.; Walsby C.J.; Williams J.A.S.; Weil J.A.; Claridge R.F.C. (My University, 2003)
X-band electron paramagnetic resonance experiments on a gamma-irradiated α-quartz crystal have revealed a new hydrogarnet-like defect. Analysis of the spectral data suggests that the centre consists of an oxygenic electron hole adjacent to a silicon vacancy, charge-compensated by a proton and two lithium +1 ions. The principal directions of the spin-Hamiltonian g matrix indicate that the oxygenic hole occurs on the oxygen ion that would be long-bonded to the missing silicon atom. Modelling of the proton and lithium hyperfine matrices via three different methods has provided a detailed physical view for the structure of the defect centre, which is presented here.
Keywords: Tonian; Precambrian::Proterozoic::Neoproterozoic::Tonian; Докембрий::Протерозой::Неопротерозойская::То́ний